2016
DOI: 10.1095/biolreprod.115.137109
|View full text |Cite
|
Sign up to set email alerts
|

Quiescence Loosens Epigenetic Constraints in Bovine Somatic Cells and Improves Their Reprogramming into Totipotency

Abstract: Reprogramming by nuclear transfer (NT) cloning forces cells to lose their lineage-specific epigenetic marks and reacquire totipotency. This process often produces molecular anomalies that compromise clone development. We hypothesized that quiescence alters the epigenetic status of somatic NT donor cells and elevates their reprogrammability. To test this idea, we compared chromatin composition and cloning efficiency of serum-starved quiescent (G0) fibroblasts versus nonstarved mitotically selected (G1) controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 85 publications
3
32
0
Order By: Relevance
“…Moreover, we found that starvation combined with vitamin C treatment induced not only 5hmC increase but also simultaneous 5mC decrease. This finding supports previous report that serum starvation facilitates epigenetic changes in cells (Kallingappa et al, ). Despite this, vitamin C treatment of the starved donor cells still failed to improve the blastocyst development of SCNT embryos, albeit the expression of some pluripotency genes ( KLF4 and SOX2 ) was significantly increased.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, we found that starvation combined with vitamin C treatment induced not only 5hmC increase but also simultaneous 5mC decrease. This finding supports previous report that serum starvation facilitates epigenetic changes in cells (Kallingappa et al, ). Despite this, vitamin C treatment of the starved donor cells still failed to improve the blastocyst development of SCNT embryos, albeit the expression of some pluripotency genes ( KLF4 and SOX2 ) was significantly increased.…”
Section: Discussionsupporting
confidence: 93%
“…2A, B). Serum starvation has been shown to globally reduce trimethylation levels in bovine fibroblasts and increase their cloning efficiency [24]. We therefore analysed the effect of Kdm4b overexpression in non-starved vs serum-starved BEFs separately.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that serum starvation about halves the amount of H3K9me3 in non-transgenic primary bovine cell types, resulting in a more relaxed chromatin structure and providing a molecular correlate for the elevated reprogrammability of quiescent donor cells into totipotency. This halving may be due to starved cells acquiring non-methylated histones during S-phase but not re-instating trimethylation upon serum starvation, allowing completion of the last DNA replication and mitosis before entering a non-proliferative G 0 state [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The population with the highest proportion of HDR events was used for manual isolation of clonal cell strains. We modified our mitotic shake-off procedure for synchronising cells in the G1 cell cycle stage to obtain sufficient starting material for isolating genome-edited clones 66,67 . Briefly, 2.5x10 4 cells/cm 2 were seeded on 4-well plate and cultured for 18-20 h. Cells were washed once with PBS and cultured for another 2-3 h before mitotic shake-off by gently tapping the dish with moderate horizontal force.…”
Section: Manual Isolation Of Clonal Cell Strainsmentioning
confidence: 99%